If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5(9n-3)=3(3-17n)
We move all terms to the left:
-5(9n-3)-(3(3-17n))=0
We add all the numbers together, and all the variables
-5(9n-3)-(3(-17n+3))=0
We multiply parentheses
-45n-(3(-17n+3))+15=0
We calculate terms in parentheses: -(3(-17n+3)), so:We get rid of parentheses
3(-17n+3)
We multiply parentheses
-51n+9
Back to the equation:
-(-51n+9)
-45n+51n-9+15=0
We add all the numbers together, and all the variables
6n+6=0
We move all terms containing n to the left, all other terms to the right
6n=-6
n=-6/6
n=-1
| -4m=1m-5 | | 10r-5r=+3r-8r | | X^2+42=16x-22 | | 5x-6=+16 | | 16x+10=16x+400 | | 1n+6=10-1n | | 2x+86+4x+48=180 | | 8(2h-3)-7=17 | | -6n+12=48 | | -2(1-3x)-29=8x-(x-23) | | X^2+21=7x+39 | | 19+x=5 | | 8x+80=240 | | 7.5=1/4x | | 10-0.25=16-0.75x | | 4(-8r-7)=154 | | -14+22=-4{x+4} | | 11.8(f)=37 | | -5(3x+1=-80 | | y/11-5=1. | | 2(y+8)=8y-26 | | (x-20)+40=180 | | 2x+86+5x-7=180 | | -5/3m=-9 | | -2u+6(u+5)=38 | | -5x+34=-7x+1 | | 3(5-5x)-4(6x+6)=-48 | | 4.8x-13.8=0.6 | | 23=18y-7+2y | | 101+3x=1-17× | | -6w+9+4w=13 | | 8x+8x=112. |